Recent Advances in Regiodivergent Cross-Dehydrogenative Coupling of Catechols - Sohtome, Yoshihiro; Kihara, Kazuki (Synthesis, 2025)
Catechols exhibit unique chemical properties owing to the presence of two hydroxyl groups on adjacent positions in the benzene ring. Although cross-dehydrogenative coupling reactions of catechols have a long-standing history, with seminal reports dating back to the mid-1890s, they have recently garnered renewed attention as strategies for accessing multisubstituted catechols. Furthermore, achieving catalyst-controlled regioselectivity in these transformations expands their synthetic utility and enables streamlined access to structurally diverse catechol derivatives. In this short review, we highlight the scope and limitations of recently developed strategies for regiodivergent cross-dehydrogenative coupling reactions of catechols. Emphasis is placed on the mechanistic principles that govern regioselectivity, thus providing a foundation for the rational design of future regiodivergent catalytic systems.
Keywords: Regioselectivity; Catechols; Cross-dehydrogenative couplings; ortho-Quinones; Persistent radicals